2016
DOI: 10.3390/v8090258
|View full text |Cite
|
Sign up to set email alerts
|

Capsid-Targeted Viral Inactivation: A Novel Tactic for Inhibiting Replication in Viral Infections

Abstract: Capsid-targeted viral inactivation (CTVI), a conceptually powerful new antiviral strategy, is attracting increasing attention from researchers. Specifically, this strategy is based on fusion between the capsid protein of a virus and a crucial effector molecule, such as a nuclease (e.g., staphylococcal nuclease, Barrase, RNase HI), lipase, protease, or single-chain antibody (scAb). In general, capsid proteins have a major role in viral integration and assembly, and the effector molecule used in CTVI functions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 101 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…Based on the combination of C protein and RNA, researchers have considered fusing exogenous genes with C protein through a capsid-targeted antiviral inactivation (CTVI) strategy [ 62 ]. This tactic is based on the fusion of the C protein and a crucial effector molecule, such as a nuclease, a lipase, a protease, or a single-chain antibody (scAb), which can degrade viral DNA/RNA or interfere with the proper folding of important viral proteins [ 63 ].…”
Section: Multiple Functions Of the C Proteinmentioning
confidence: 99%
“…Based on the combination of C protein and RNA, researchers have considered fusing exogenous genes with C protein through a capsid-targeted antiviral inactivation (CTVI) strategy [ 62 ]. This tactic is based on the fusion of the C protein and a crucial effector molecule, such as a nuclease, a lipase, a protease, or a single-chain antibody (scAb), which can degrade viral DNA/RNA or interfere with the proper folding of important viral proteins [ 63 ].…”
Section: Multiple Functions Of the C Proteinmentioning
confidence: 99%
“…Moreover, the result of direct inactivation of the virus particle demonstrated that the non-sericin extract had the most virucidal effect against both HSV-1 and HSV-2 in a dose and time-dependent manner ( Figure 2 ). We hypothesized that bioactive compounds in non-sericin extract might contribute to the inhibition through deconstructing the virion envelope structure or inducing the glycoprotein conformational change [ 32 , 33 , 34 ]. However, further investigation is needed to demonstrate the effect of extracts on viral structure i.e., cryo-EM to reveal changes of the virus surface.…”
Section: Discussionmentioning
confidence: 99%
“…423–439]. The virus capsid assembly and DNA packaging have been proposed to be the target for antiviral therapy [ 34 ]. Thus, biofilm formation may share a similar group of involved genes with viral procapsid maturation and biofilm formation may be suggested as the target for antimicrobial treatment.…”
Section: Discussionmentioning
confidence: 99%